Analysis of Code Mixing and Code Switching Pavolia Reine’s Live Stream - Setiawan, Frans; Eldi Putra, Fiqry; Fitriyah, Fitriyah (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study investigates the use of code-mixing and code-switching in Pavolia Reine’s live streams, applying sociolinguistic frameworks by Poplack and Muysken to analyze these phenomena in a live-streaming context. Using a qualitative descriptive method, data were collected through transcriptions of her streams, focusing on identifying and categorizing instances of code-mixing and code-switching. The findings show that insertional code-mixing dominates, accounting for 97% of all cases, while alternation and congruent lexicalization represent 2% and 1%, respectively. This reflects the bilingual and multicultural environment of Hololive Indonesia, where Indonesian speakers frequently incorporate English and Japanese to reach broader audiences. Inter-sentential switching is the most common form of code-switching at 53%, followed by intra-sentential switching (29%) and tag switching (18%). These patterns demonstrate how linguistic strategies are employed to connect with local and international viewers, highlighting the multilingual backgrounds of the speakers. Overall, the study underscores the complexity and fluid integration of multiple languages in online streaming, illustrating how digital communication reshapes linguistic practices in real time